A Comparative Study of the Relationship between Conservatism with Basu’s and Ball & Shivakumar’s Methods - Abedini, Bizhan; Salehi, Mahdi (Serbian Journal of Management, 2012)
The current study aims to investigate the relationship between conservatism of profit and the ratio of the market value to book value with Basu’s and Ball & Shivakumar’s methods in Iran. For this purpose, 155 listed companies in Tehran Stock Exchange consider as sample of the study during 2004-2010. In this context, it is used two methods (Basu and Ball & Shivakumar’s Models) to measure conservatism of profit. According to calculations and using regression, the obtained results shows that there is no significant relation between conservatism of profit and the ratio of the market value to book value in both employed methods of conservatism.